Effects of blood processing and sample storage on the stability of biotherapeutics and anti-drug antibodies. (June 2015) - Andisik, Matthew; DeStefano, Lisa; Stefan, Colin; Gathani, Meghna; Laurino, Kevin; Lai, Vicky CH; Rajadhyaksha, Manoj; Torri, Albert; Shao, Weiping
Background: Pre-analytical factors such as sample processing, handling or storage could affect the stability of biotherapeutics and anti-drug antibodies in clinical samples, potentially impacting the pharmacokinetic and immunogenicity assessments.Methods: We used sarilumab, a fully human IgG1 monoclonal antibody, and evaluated the stability of sarilumab (both functional and bound forms) and anti-sarilumab antibodies in blood samples during serum collection and the impact of various processing conditions on the analyte stability in serum for long-term storage. We also assessed the incurred sample stability of these analytes in samples from clinical studies.Conclusion: Assessment of analyte stability can provide relevant information about sample stability under different pre-analytical conditions and improve the confidence in the validity of bioanalytical data generated.